Factors Influencing Anesthesia Technicians in Providing Anesthesia Education to Surgical Patients with Cardiovascular Disorders - Putu Atika Parwati; Sang Ketut Arta; Luh Gde Nita Sri Wahyuningsih (GLOBAL HEALTH SCIENCE GROUP, 2024)
Education on anesthesia for cardiovascular disorders includes matters related to anesthesia from pre, intra, to post anesthesia and will affect how prepared the patient is to face post-anesthesia conditions. Education on anesthesia has not been implemented optimally, its implementation only focuses on pre-anesthesia preparation, while for intra and post anesthesia its implementation has not been optimal. This is influenced by several factors. Through this study, we want to know the factors that influence anesthesiologists in providing education on anesthesia procedures in surgical patients with cardiovascular disorders. The research design used was a correlation analytic study with a cross-sectional approach. The population taken was anesthesiologists in Indonesia with a purposive sampling technique. The sample in this study was 254 anesthesiologists with a purposive sampling technique. Bivariate analysis with the chi square test was carried out to test the factors that influence anesthesiologists in providing education on anesthesia procedures in surgical patients with cardiovascular disorders. The results of the study concluded that work patterns had a significant relationship with the provision of education (p <0.001), while length of work (p 0.823) and workload (p 0.113) were not significantly related to the level of education provision. Further research is recommended on the dominant factors that influence the provision of education on anesthesia procedures in surgical patients with cardiovascular disorders.